Introduction: The Startup Process - Acs, Zoltan (Estudios de Economía, 2016)
Entrepreneurship is considered to be an important mechanism for economicdevelopment through employment, innovation and welfare effects. The papersin this special issue are from the 3rd Global Entrepreneurship Monitor ResearchConference held in Washington D.C. in 2007. The introduction has three objectives.First, to discuss the importance of the three stages of economic development,the factor-driven stage, the efficiency-driven stage and the innovation-drivenstage. Second, to examine the empirical evidence on the relationship betweenstages of economic development and entrepreneurship. Third, to present asummary of the papers.